PENGEMBANGAN MODUL PEMBELAJARAN ILMU EKONOMI BERBASIS TECHNOPRENEURSHIP DI UNIVERSITAS NEGERI GORONTALO - Herwin Mopangga (Jurnal Profit Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
Abstract : This research aims to know how about the level of students understanding and masteringof economics, and to develop learning module of economics based on technopreneurship. Used descriptive and qualitative approach where the process preceded by observation and identification learning of economics and entrepreneurship applied in 15 program undergraduate studies and a diploma in State University of Gorontalo (UNG). Data collection by documentation, literature study and questioner to 100purposive students.Research concluded that 1) students aware that the importance to understand and analysedof the development of economics not only for the benefit of academic but also to create of new jobs, 2 ) the results of economics learning 2014/2015 in UNGshows quite satisfactory based on percent comparison stayed on course for a value of A, B and C each 36, 50 and 14 percent, 3)learning more attractive and right on target, need to enriched with learning module of economics that are contextual and applicative.Module has help students to understand social reality as an unemployment intellectual and the importance of improving activities on innovative entrepreneurial.For local people in Gorontalo especially UNG, technopreneurship is well known relatively new even foreign to some students.There should be deepening and expansion of research and development activities to values technopreneurship who aims for increasing the quality of human resources and those competitivenessto face the implementation of ASEAN Economic Community 2016.Abstrak : penelitian ini bertujuan untuk mengetahui tingkat pemahaman dan keahlian siswa dalam ilmu ekonomi dan mengembangkan model pembelajaran ekonomi berbasis technopreneurship. Pendekatan dalam penelitian ini yaitu deskriptif dan kualitatif dengan melakukan observasi dan mengidentifikasi pembelajaran ekonomi dan kewirausahaan di 15 program studi S1 dan diploma di Universitas Negeri Gorontalo (UNG). Data di peroleh melalui dokumentasi, dan angket dari 100 mahasiswa. Kesimpulan penelitian yaitu 1) mahasiswa Mahasiswa menyadari pentingnya mempelajari, memahami dan menganalisis perkembangan ilmu ekonomi bukan hanya untuk kepentingan akademis tetapi juga untuk penciptaan lapangan kerja baru di masyarakat. 2) Hasil belajar Ilmu Ekonomi di UNG pada tahun akademik 2014/2015 menunjukkan hasil cukup memuaskan berdasarkan pada persentasi perbandingan raihan nilai A, B dan C masing-masing 36, 50 dan 14 persen. 3) Agar proses pembelajaran lebih menarik dan tepat sasaran, perlu diperkaya dengan modul pembelajaran ilmu ekonomi yang kontekstual dan aplikatif. Modul tersebut memudahkan mahasiswa memahami realitas sosial seperti meningkatnya angka pengangguran intelektual dan pentingnya meningkatkan kegiatan wirausaha inovatif. Bagi masyarakat lokal Gorontalo khususnya UNG, technopreneurship adalah konsep yang relatif baru dikenal bahkan masih asing bagi sejumlah mahasiswa. Perlu ada pendalaman serta perluasan kegiatan riset dan pengembangan terhadap nilai-nilai technopreneurship yang bertujuan peningkatan kualitas SDM dan daya saingnya menghadapi pemberlakuan Masyarakat Ekonomi ASEAN 2016 mendatang